Periapical bone response to bacterial lipopolysaccharide is shifted upon cyclooxygenase blockage - Fernanda Regina Ribeiro-Santos; Geyson Galo da Silva; Igor Bassi Ferreira Petean; Maya Fernanda Manfrin Arnez; Léa Assed Bezerra da Silva; Lúcia Helena Faccioli; Francisco Wanderley Garcia Paula-Silva
Abstract Objectives: Infection, inflammation and bone resorption are closely related events in apical periodontitis development. Therefore, we sought to investigate the role of cyclooxygenase (COX) in osteoclastogenesis and bone metabolism signaling in periapical bone tissue after bacterial lipopolysaccharide (LPS) inoculation into root canals. Methodology: Seventy two C57BL/6 mice had the root canals of the first molars inoculated with a solution containing LPS from E. coli (1.0 mg/mL) and received selective (celecoxib) or non-selective (indomethacin) COX-2 inhibitor. After 7, 14, 21 and 28 days the animals were euthanized and the tissues removed for total RNA extraction. Evaluation of gene expression was performed by qRT-PCR. Statistical analysis was performed using analysis of variance (ANOVA) followed by post-tests (α=0.05). Results: LPS induced expression of mRNA for COX-2 (Ptgs2) and PGE2 receptors (Ptger1, Ptger3 and Ptger4), indicating that cyclooxygenase is involved in periapical response to LPS. A signaling that favours bone resorption was observed because Tnfsf11 (RANKL), Vegfa, Ctsk, Mmp9, Cd36, Icam, Vcam1, Nfkb1 and Sox9 were upregulated in response to LPS. Indomethacin and celecoxib differentially modulated expression of osteoclastogenic and other bone metabolism genes: celecoxib downregulated Igf1r, Ctsk, Mmp9, Cd36, Icam1, Nfkb1, Smad3, Sox9, Csf3, Vcam1 and Itga3 whereas indomethacin inhibited Tgfbr1, Igf1r, Ctsk, Mmp9, Sox9, Cd36 and Icam1. Conclusions: We demonstrated that gene expression for COX-2 and PGE2 receptors was upregulated after LPS inoculation into the root canals. Additionally, early administration of indomethacin and celecoxib (NSAIDs) inhibited osteoclastogenic signaling. The relevance of the cyclooxygenase pathway in apical periodontitis was shown by a wide modulation in the expression of genes involved in both bone catabolism and anabolism.